The City planned through the Production of Housing: A Review of Three Housing Complexes by Corvi in Chile (1961-1965) - Ibarra, Macarena; Ortega-Esquivel, Andrea (Revista de Urbanismo, 2023)
n the understanding that housing was a key element in urban planning during the 1961-1965 period, this article examines the way in which the State materialized its planning role through an ad hoc institutionality and its expression in various regional contexts in Chile. Based on two criteria, geographical and typological, three initiatives are analyzed: El Morro Remodeling, Iquique; Ignacio Zenteno Housing Complex in Cerro Lecheros, Valparaíso; and Villa San Pedro township, in Coronel. These cases allow us to examine the housing proposal in its relation with the city through the Housing Corporation (CORVI). The sources used —mainly institutional memories, periodical publications, and records of the initiatives studied— are put into perspective under a methodology that compares the three selected cases that are characterized by different geographical situations and project strategies: remodeling, complex, and township. While the remodeling of Iquique sought to generate contrast through the horizontality of the block, in the Valparaíso complex, on the other hand, the block breaks to adapt to the slope; and in the town of Coronel, a garden city with a wide diversity of uses was planned on the outskirts of the city. This reflects different ways in which the city was planned, adapting to different urban and landscape contexts, but under the same logic of housing provision in a period in which the city was the subject of social, urban, and political debate.